1973
DOI: 10.1097/00004032-197311000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic Dental Radiography for Mass Screening?

Abstract: Dental panoramic radiography has increased in popularity and use since its introduction in the late 1950's and proposals have been made to apply this methodology as a mass screening tool. Ease of examination and the reportedly low radiation exposure to the anterior superficial tissues have been cited as reasons for this application. However, in panoramic radiography the X-ray beam enters posteriorly which results in high doses to posterior and to internal tissues. We have employed LiF thermoluminescent dosimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Wall, E. S. Fisher, R. Paynter, A. Hudson and P. D. Bird Panorex are generally lower than reported elsewhere (Kuba and Beck 1968;Howley et al, 1968;Jerman et al, 1973, Bushong et al, 1973. This may well be due to the lower current of 5 mA considered adequate for good radiographs on present day machines in this country compared with the 10 mA used a few years ago in the United States.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Wall, E. S. Fisher, R. Paynter, A. Hudson and P. D. Bird Panorex are generally lower than reported elsewhere (Kuba and Beck 1968;Howley et al, 1968;Jerman et al, 1973, Bushong et al, 1973. This may well be due to the lower current of 5 mA considered adequate for good radiographs on present day machines in this country compared with the 10 mA used a few years ago in the United States.…”
Section: Resultsmentioning
confidence: 59%
“…Jerman et al (1973) came to a similar conclusion after comparing the doses from a Panorex scan plus bitewing exposures against a full-mouth periapical series plus bitewing exposures, using calcium fluoride dosemeters on patients. Bushong et al (1973) measured doses to the surface of a head phantom with lithium fluoride chips and concluded that the skin doses of between 0.2 cGy and 0.26 cGy to the lateral and posterior aspects of the head from a Panorex exposure were too high to justify large scale mass screening using this technique.…”
Section: Previous Studiesmentioning
confidence: 99%